Interactive Puzzle Based on Gamification Concepts Assisted by a Website on the Five Senses Material to Improve Learning Outcomes of Fourth-Grade Elementary School Students - Anna Shau Tong; I Gede Margunayasa; I Wayan Widiana (Universitas Pendidikan Ganesha, 2026)
The low science learning outcomes of fourth-grade elementary school students on the five senses material are generally caused by the lack of variety and interactivity of the learning media used, so that students tend to be passive and easily bored. This study aims to develop and test the feasibility of innovative learning media in the form of interactive puzzles that integrate the concept of gamification with the help of websites to improve student learning outcomes. This study uses a research and development method (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The product was assessed by media experts and material experts, and its practicality was tested by teachers and fourth-grade students of SD Negeri 2 Kalibukbuk. The effectiveness of the media was measured using a one-group pretest–posttest design. The validation results showed that the media obtained an average score of 3.83 with a very good category. The practicality test showed a percentage of 100% from teachers and 98% from students with a very good category. Paired sample t-test analysis showed a significant difference between the pretest and posttest scores (p < 0.05) which proved the effectiveness of the learning media. The implications of this research indicate that the use of interactive puzzle media based on gamification and a website can be an alternative solution for more engaging and meaningful science learning, while encouraging active student engagement. This media can be utilized by teachers as a digital learning innovation. The conclusion of this research is that the developed media is valid, practical, and effective in improving the learning outcomes of fourth-grade elementary school students in the five senses material.